2015
DOI: 10.17109/azh.61.4.373.2015
|View full text |Cite
|
Sign up to set email alerts
|

Habitat urbanization and its effects on birds

Abstract: By transforming landscapes, human activity creates new types of habitats with altered environmental characteristics that never existed before. As the process of habitat urbanization bears impact on more and more natural habitats, it is essential for us to understand the changes we bring forth in the ecological forces shaping urban animal communities. Birds are perhaps the most frequently studied model organisms by urban ecologists. It is a well known general pattern that urban avian communities have typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
135
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(159 citation statements)
references
References 146 publications
(195 reference statements)
3
135
0
3
Order By: Relevance
“…Certainly, food availability is an important factor acting to limit bird populations (Newton, 1980), affecting reproductive success and survival of many bird species in different systems (Martin, 1987). Despite the additional deliberate (i.e., bird feeding) and unintentional (e.g., refuse) food resources available to birds in urban systems, demand for food can be high due to high bird densities reducing the per capita amount of food available (Seress and Liker, 2015). This demand is illustrated by an experimental study in Arizona, USA, that found supplementary food in urban areas was depleted much faster than equivalent amounts provided in natural habitats (Shochat et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, food availability is an important factor acting to limit bird populations (Newton, 1980), affecting reproductive success and survival of many bird species in different systems (Martin, 1987). Despite the additional deliberate (i.e., bird feeding) and unintentional (e.g., refuse) food resources available to birds in urban systems, demand for food can be high due to high bird densities reducing the per capita amount of food available (Seress and Liker, 2015). This demand is illustrated by an experimental study in Arizona, USA, that found supplementary food in urban areas was depleted much faster than equivalent amounts provided in natural habitats (Shochat et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies, though, have looked at individual variation in supplementary food use or how species associations at feeders affect resource access in an urban context specifically (but see Cowie and Hinsley, 1988;Crates et al, 2016;Jack, 2016). Bird populations in urban habitats are subject to different pressures than those in more natural environments, frequently resulting in differences in ecology, behavior, and life history (Chace and Walsh, 2006;Chamberlain et al, 2009;Seress and Liker, 2015;Garcia et al, 2017;Lepczyk et al, 2017). Furthermore, urban areas, particularly in New Zealand, are hotspots for introduced (i.e., nonnative/exotic/alien) bird species (Day, 1995;Duncan et al, 2003;van Heezik et al, 2008;Spurr, 2012;Davis et al, 2014), with bird feeding implicated in the success of some of these species (Strubbe and Matthysen, 2007;Peck et al, 2014;Orros and Fellowes, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…At the population level, noise pollution was found to induce an increased pitch in birds or a shift in their singing activity to the night time, avoiding noisy periods (Slabbekoorn and Peet, 2003;Kirschel et al, 2009;Nemeth and Brumm, 2009). Artificial night lighting-light pollution-may attract many birds during their nocturnal migration: harsh consequences for such important detours are an increased number of predation events and/or collisions with artificial structures in cities (van de Laar, 2007, reviewed in Erritzoe et al, 2003, as well as a reduction in energy storage or delayed arrival at wintering or breeding areas (Seress and Liker, 2015). Light pollution can also affect bird behaviour by advancing avian singing time at dawn and dusk (Da Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to natural areas, urban habitats are characterized by many altered environmental factors such as elevated levels of chemical, noise and light pollution, transformed landscapes or various disturbances resulting from the increased human population (Marzluff et al, 2001b;Sol et al, 2013;Sprau et al, 2016). These altered environmental factors impact ecological factors that affect population dynamics and persistence, such as food availability and predation pressure (Seress and Liker, 2015). As a consequence, interspecific interactions such as predator-prey relationships can differ qualitatively between urban and non-urban habitats (Faeth et al, 2005;Chace and Walsh, 2006;Fischer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%